2021
DOI: 10.1016/j.heliyon.2021.e06934
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic items delivery network: prediction and clustering

Abstract: Items delivery companies generally use a model to minimize delivery costs. From a mathematical perspective, the model is an objective function that involves constraints. Meanwhile, from a practical point of view, these constraints include aspects that affect item delivery, for example, delivery zones, number of delivery vehicles, vehicle capacity, trip routes, etc. However, the models built so far have not paid attention to changes in road density. This aspect can result in a nonoptimal delivery model, which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Quantitative data were analyzed using k-means clustering and correspondence analysis. K-mean clustering was performed to find students' similarities based on their ISC and classify them into several groups (Yudhanegara et al, 2021). In this clustering, the number of clusters is determined at the beginning, then the researcher identifies and interprets the clusters formed subjectively (Yudhanegara et al, 2020a(Yudhanegara et al, , 2020b.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative data were analyzed using k-means clustering and correspondence analysis. K-mean clustering was performed to find students' similarities based on their ISC and classify them into several groups (Yudhanegara et al, 2021). In this clustering, the number of clusters is determined at the beginning, then the researcher identifies and interprets the clusters formed subjectively (Yudhanegara et al, 2020a(Yudhanegara et al, , 2020b.…”
Section: Discussionmentioning
confidence: 99%
“…We will use the clustering method to get the best prediction model in future research [12]- [15]. It also compares the prediction results between the Poisson regression and the predictive distribution methods [16] and statistical inference for online decision [17].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, if the resulting data does not change the distribution, the learning model tends not to change [8] [9]. In general, if the data obtained does not change the distribution, then the learning model tends not to change.…”
Section: Statistics Coursementioning
confidence: 99%
“…In this study, the vector ๐›‰ is the observed value of the random vector ๐šฏ. The random vector ๐šฏ has a distribution that acts as the prior of the multinomial, with ๐šฏ coming from the Dirichlet distribution [8]. Then look for the conditional probability distribution for the observation ๐ฑ ๐‘ก+๐‘˜ if given the observation…”
Section: Predictive Distribution For Multinomial Casementioning
confidence: 99%